Evaluation of digital optical density of bone repair in rats medicated with ketoprofen - Martins, Mãrcia Valẽria [UNESP]; Da Silva, Marcos Andrẽ Dos Santos [UNESP]; Medici Filho, Edmimdo [UNESP]; De Moraes, Luiz Cesar [UNESP]; Castilho, Julio Cezar De Melo [UNESP]; Da Rocha, Rosilene Fernandes [UNESP] (Springer Nature, 2005)
The purpose of this study was to evaluate the influence of ketoprofen on bone repair process in tibiae of rats by means of analysis of the digital optical density. Twenty Wistar rats were assigned to two groups: an untreated control group and a group treated with ketoprofen. The experimental procedures comprised the following stages: general anesthesia, preparation of a unicortical bone defect on the left tibia of each rat, medication with ketoprofen and radiographic examination. Digital radiographic images were acquired using Visualix GX-S-HDI™ digital sensor and an x-ray equipment. Radiographs were taken at baseline, 7, 14, 21 and 30 days postoperatively and the optical density (OD) was evaluated using the Vix win™ 1.4 system. The mean values of OD readings were analyzed statistically by ANOVA and Tukey's test with significance level set at á=5%. The control group showed a statistically significant correlation (p=0.001) between time and optical density, while the ketoprofen group exhibited a weak and not statistically significant correlation (p=0.100). The control group presented the smallest OD ratios at days 1 and 7, and the greatest OD ratios at days 14, 21 and 30, with statistically significant difference (p=0.001). There was no significant differences (p=0.100) among the OD ratios in the ketoprofen group, regardless of the evaluation period. The findings of this study suggest that ketoprofen influenced bone repair process because there was an increase in optical density during the first week and delayed new bone formation after the 21st day.
Keywords: Bone repair; Digital optical density; Direct digital radiograph; Ketoprofen